Higher Blood Glucose within the Normal Range Is Associated with More Severe Strokes - Rolf J. Martin; Rajiv R. Ratan; Michael J. Reding; Tom S. Olsen (Stroke Research and Treatment)
Background. Higher fasting blood glucose (FBG) concentrations in the hyperglycemic range are associated with more severe strokes. Whether this association also extends into patients with FBG in the normoglycemic range is unclear. We studied the association of stroke severity and FBG in normoglycemic patients with ischemic stroke in a median of 7 days after stroke when the initial glycemic stress response has resolved. Method and Material. Included were 361 nondiabetic ischemic stroke patients with admission fasting blood glucose within 70–130 mg/dL admitted into an acute stroke rehabilitation unit in a median of 7 days after stroke. Data including neuroimaging, vital signs, cardiovascular risk factors, and admission functional independence measure (AFIM) were recorded prospectively. Results. FBG correlated with stroke severity in the normoglycemic 70–130 mg/dL range (FBG-AFIM correlation coefficient −0.17; P=0.003). Odds ratio for more severe injury (below average AFIM score) was 2.02 for patients with FBG 110–130 mg/dL compared to FBG 70–90 mg/dL (95% confidence interval 1.10–3.73, P=0.022). Each mg/dL increase in FBG was associated with an average decrease of 0.25 FIM points. In a multiple linear regression model, FBG was associated with more severe stroke (P=0.002). Conclusion. One week after ischemic stroke, FBG within the normoglycemic range was associated with stroke severity.